The impact of deforestation, urbanization, public investments, and agriculture on human welfare in the Brazilian Amazonia. (June 2017) - Silva, José Maria Cardoso da; Prasad, Shivangi; Diniz-Filho, José Alexandre Felizola
Highlights: We evaluated changes in human welfare in the Brazilian Amazonia from 2005 to 2012. Signals of a boom-and-bust pattern are weak at the regional and state level. Urbanization does not lead to positive changes in human welfare. Public investments and agriculture are negatively associated with human welfare growth. State-level policies influence regional trends in human welfare. Abstract: The relationship between human welfare and deforestation in the Brazilian Amazonia has traditionally been thought to follow a boom-and-bust pattern. According to this pattern, forest clearing triggers rapid increases in human welfare levels ("the boom") due to short-term economic gains; these levels then drop to below national or regional averages ("the bust") after the forest stocks have declined, thus causing the local populations to become deprived of ecosystem services. However, recent studies have questioned the validity of this boom-and-bust pattern. In this paper, we use panel data and simultaneous autoregressive models to evaluate the effects of deforestation, urbanization, public investments, agriculture, and state policies on temporal changes in human welfare that occurred across multiple municipalities in the Brazilian Amazonia from 2005 to 2012, a period during which governments implemented a set of strategies aimed at controlling deforestation across the region. We found that: (a) signals of a boom-and-bust pattern are weak at the regional level, and therefore this pattern cannot be generalized across the entire region; (b) human welfare is increasing more rapidly in low-development municipalities than in high-development cities, and all municipalities are converging on at least one regional average rather than on a national average; (c) urbanization does not lead to positive changes in human welfare, which indicates that the infrastructure available in regional urban centers is limited; (d) public investments are negatively associated with human welfare growth, thus signifying that if public investments are not used to leverage the potential of other sectors of the local economy, human welfare will not improve; (e) agriculture is negatively associated with positive changes in human welfare at the local level, possibly due to the dominance of cattle-ranching as the predominant economic activity of this sector; and (f) state-level policies matter, and future analyses of regional trends in the realm of development and conservation across this region should take such policies into account. Finally, we suggest that although human welfare and deforestation retain a weak statistical relationship, we cannot contend that they have been fully decoupled. Forest loss across the region is still pervasive, and institutions are too weak to sustain the transition from a frontier development model to a conservation-centered model.